Lessons learned from the London Exercise and Pregnant (LEAP) Smokers randomised controlled trial process evaluation: implications for the design of physical activity for smoking cessation interventions during pregnancy - Giatras, Nikoletta; Wanninkhof, Elisabeth; Leontowitsch, Miranda; Lewis, Beth; Taylor, Adrian; Cooper, Sue; Ussher, Michael (BioMed Central, 2017)
Background: The challenges of delivering interventions for pregnant smokers have been poorly documented. Also, the process of promoting a physical activity intervention for pregnant smokers has not been previously recorded. This study describes the experiences of researchers conducting a randomised controlled trial of physical activity as an aid to smoking cessation during pregnancy and explores how the effectiveness of future interventions could be improved.